2022
DOI: 10.48550/arxiv.2203.00105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parameterizations of black-hole spacetimes beyond circularity

Héloïse Delaporte,
Astrid Eichhorn,
Aaron Held

Abstract: We discuss parameterizations of black-hole spacetimes in and beyond General Relativity in view of their symmetry constraints: within the class of axisymmetric, stationary spacetimes, we propose a parameterization that includes non-circular spacetimes, both in Boyer-Lindquist as well as in horizon-penetrating coordinates. We show how existing parameterizations, which make additional symmetry assumptions (first, circularity; second, a hidden constant of motion), are included in the new parameterization. Further,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…For the discussion on noncircular spacetimes and their observational implications, we refer the readers to Refs. [87][88][89][90].…”
Section: Deformed Schwarzschild Spacetimementioning
confidence: 99%
“…For the discussion on noncircular spacetimes and their observational implications, we refer the readers to Refs. [87][88][89][90].…”
Section: Deformed Schwarzschild Spacetimementioning
confidence: 99%
“…In general, such approaches are highly non-unique and theory agnostic in nature. Several interesting regularized BH solutions (both static and rotating) have been proposed over years [4][5][6][7][8][9][10][11][12][13]. Such solutions contain one or more additional parameters over the usual hairs, namely the mass and spin of a Kerr BH.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, a Taylor expansion in terms of the cosine function of the angular variable is taken. On the other hand, Delaporte, Eichhorn and Held [8] discussed the parameterizations of black-hole spacetimes in and beyond General Relativity and showed that the existing parameterizations are included in their new parameterizations.…”
Section: Introductionmentioning
confidence: 99%